2020
DOI: 10.1021/acs.est.0c01951
|View full text |Cite
|
Sign up to set email alerts
|

Legacy and Novel Per- and Polyfluoroalkyl Substances in Juvenile Seabirds from the U.S. Atlantic Coast

Abstract: Per-and polyfluoroalkyl substances (PFAS) are anthropogenic, globally distributed chemicals. Legacy PFAS, including perfluorooctane sulfonate (PFOS), have been regularly detected in marine fauna but little is known about their current levels or the presence of novel PFAS in seabirds. We measured 36 emerging and legacy PFAS in livers from 31 juvenile seabirds from Massachusetts Bay, Narragansett Bay, and the Cape Fear River Estuary (CFRE), United States. PFOS was the major legacy perfluoroalkyl acid present, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 94 publications
1
38
0
Order By: Relevance
“…The starkly different environmental characteristics of breeding vs. non-breeding ranges have previously been demonstrated to expose Great Shearwaters to higher levels of humanderived pollutants compared to other seabirds from the same breeding location that solely rely on South Atlantic environments (Roscales et al, 2019;Robuck et al, 2020). We believe a similar dynamic is driving the physical characteristics of plastic items observed in this study.…”
Section: Size-mediated Environmental Distribution Of Plastics Is Reflected In Great Shearwater Plastic Ingestionsupporting
confidence: 63%
“…The starkly different environmental characteristics of breeding vs. non-breeding ranges have previously been demonstrated to expose Great Shearwaters to higher levels of humanderived pollutants compared to other seabirds from the same breeding location that solely rely on South Atlantic environments (Roscales et al, 2019;Robuck et al, 2020). We believe a similar dynamic is driving the physical characteristics of plastic items observed in this study.…”
Section: Size-mediated Environmental Distribution Of Plastics Is Reflected In Great Shearwater Plastic Ingestionsupporting
confidence: 63%
“…These CTVs, exposure concentrations, and mixture ratios are within both biotic and abiotic PFAS environmental sampling ranges (Anderson et al, 2016; Custer et al, 2019; East et al, 2020; Filipovic et al, 2015; Gebbink & Letcher, 2012; Holmström & Berger, 2008; Nordén et al, 2013; Robuck et al, 2020). These values are also comparable to the northern bobwhite quail adult and offspring liver‐tissue LOAEL CTVs of 21.4 and 23.7 ng PFOS/g wet weight, 36.6 ng PFOS plus 15.4 ng PFHxS and 19.9 ng PFOS plus 4.16 ng PFHxS/g wet weight (Dennis, Subbiah, et al, 2021; Table 4) for exposures to 18.7 ng/ml PFOS and 22.9 ng/ml PFOS:PFHxS (1.2:1), respectively.…”
Section: Resultsmentioning
confidence: 92%
“…Environmental sampling of adult and/or juvenile liver from wild bird populations exposed to a host of PFAS concentrations and compositions indicate a broad range of PFOS, PFHxS, and PFHxA residue values (e.g., from less than detection limit–583 ng/g wet wt; see Custer et al, 2019; Gebbink & Letcher, 2012; Holmström & Berger, 2008; Nordén et al, 2013; Robuck et al, 2020). This range brackets residues (corresponding to chronic oral toxicity) quantified from the liver of adult and/or juvenile northern bobwhite quail specimens (less than detection limit–133.8 ng/g wet wt; see: Dennis, Subbiah, et al, 2021, repository data) exposed to PFOS and PFHxS at concentrations and mixture ratios typically found in the environment (Anderson et al, 2016; Dennis et al, 2020; East et al, 2020; Filipovic et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Not only do PFAS appear to be toxic in terrestrial mammals, there is significant evidence that PFAS accumulate and have toxic effects in aquatic mammals, birds, fish, amphibians, reptiles, and numerous invertebrates [91,148,[151][152][153][154][155]. In detailed studies of the Great Lakes region of the US, PFAS have been reported in various trophic levels of the aquatic food chain with concentrations of PFAS in benthic invertebrates 1000-fold greater that the surrounding water and biomagnification factors of 5-10 between the livers of salmon and the livers of eagles and mink [82].…”
Section: Health Impacts Of Pfas 61 Animal Toxicology Studiesmentioning
confidence: 99%
“…The overwhelming majority of the toxicological studies on PFAS have investigated specific legacy compounds such as PFOA and PFOS; however, in recent years, these compounds have been replaced by emerging PFAS subclasses including PFECAs in industrial processes. There are public health and environmental concerns regarding the replacement compounds, as recent studies have shown that PFECAs and a novel PFESA (referred to as Nafion byproduct 2) are now appearing in drinking water sources as well as in juvenile seabirds [155] and striped bass [91] from Atlantic coastal regions of the US. There is limited toxicological data on most PFECAs; however, HFPO-DA, which was developed as the primary replacement for PFOA, has been investigated in a number of studies.…”
Section: Health Impacts Of Pfas 61 Animal Toxicology Studiesmentioning
confidence: 99%